Kepemimpinan Instruksional Kepala Sekolah SD Negeri 02 Kandis Kota dalam Meningkatkan Profesionalisme Guru melalui Komunitas Belajar - manda, Putri; Herlinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the instructional leadership of the principal at SD 02 Kandis in enhancing teacher professionalism through learning communities. The subjects were the principal and teachers involved in learning community activities. Data were collected using interviews, observations, and document analysis, then analyzed through data reduction, data display, and drawing conclusions. The results show that the principal has a strategic role as a facilitator, planner, and motivator in implementing structured learning communities, which significantly contribute to improving teacher competence and professionalism.